2010
DOI: 10.1186/1745-6215-11-41
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic multi-centre randomised controlled trial of fluid loading and level of dependency in high-risk surgical patients undergoing major elective surgery: trial protocol

Abstract: BackgroundPatients undergoing major elective or urgent surgery are at high risk of death or significant morbidity. Measures to reduce this morbidity and mortality include pre-operative optimisation and use of higher levels of dependency care after surgery. We propose a pragmatic multi-centre randomised controlled trial of level of dependency and pre-operative fluid therapy in high-risk surgical patients undergoing major elective surgery.Methods/DesignA multi-centre randomised controlled trial with a 2 * 2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Although it must be identified that some of this reduction in employment is due to retirements. This change in employment status speaks to the broad long-term financial impact of severe sepsis on patients and their families [ 15 , 18 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it must be identified that some of this reduction in employment is due to retirements. This change in employment status speaks to the broad long-term financial impact of severe sepsis on patients and their families [ 15 , 18 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been a focus of sustained effort in orthopedic circles with a reduction in mortality in hospital after orthopedic admission recorded in recent years by SASM (http://www.sasm.org). Such an approach of optimization has been successful in cardiovascular circles [28] and is in clinical trials for more general surgical procedures [29].…”
Section: Discussionmentioning
confidence: 99%
“…This was a multi-centre, prospective, randomised, controlled trial conducted in four Scottish hospitals, coordinated from the Centre for Healthcare Randomised Trials in the Health Services Research Unit, University of Aberdeen [ 20 ]. The trial was designed as a partial 2*2 factorial design with initial randomisation to fluid loading versus no fluid loading, with a secondary randomisation (if an ICU bed was available at the time of recruitment) to intensive care (level 3) versus high dependency (level 2) care [ 20 ]. The second randomisation had to be abandoned, however, due to a continuing lack of ICU beds at the time of patient recruitment (this decision was agreed upon with the funder, the Data Monitoring Committee (DMC) and the Trial Safety Committee (TSC).…”
Section: Methodsmentioning
confidence: 99%
“…The full power calculation is presented in the trial protocol paper [ 20 ]. For the fluid comparison, we aimed to be able to detect a 0.5 SD difference in the primary outcome of number of days in hospital following surgery, with 80% power and 5% significance.…”
Section: Methodsmentioning
confidence: 99%